Fund attributes and performance in Malaysian collective investment market / Mohd Sharin Sahak - Sahak, Mohd Sharin (2019)
A performance measurement of unit trust portfolios has attracted a remarkable interest in economic and financial literature. Since then, a number of researchers have looked for the answers to whether unit trust earn a better return than what investors can earn on their own, and whether fund managers have a superior ability to make better investments than other investors. Therefore, this study conducted in order to examine the relationship between unit trust attributes and unit trust performance. In this study, unit trust performance is measured by using net asset value (NAV) and the unit trust attributes measured by using expense ratio (ER), fund size (F.SIZE) and fund turnover (FTO). Using the data covering a period of 7 years (2013-2019) of 12 Malaysian unit trust management company that listed in Bursa Malaysia with 33 funds selected. The relationship between the unit trust performance and unit trust attributes was examined by using the panel data analysis. Findings of the study showed that on fund size has significant positive relationship with the unit trust performance, while ER and FTO shows an insignificant negative relationship with the unit trust performance.